Systematic review: Barcode link modules for interactive science and math learning in Indonesian High Schools - Fransiska Romana Febrianti; Mohammad Masykuri; Endang Susilowati (Research and Development in Education (RaDEn), 2024)
There are still researchers who point out the need to strengthen the theoretical framework in developing QR-code based modules. Most of the articles reviewed pointed out relevant limitations or broader methods and a lack of mapping towards the use of QR-code based modules. This research aims to explore previous research related to the development of barcode-based modules (QR-Code) used in learning, especially for science and mathematics students in high schools in Indonesia. The authors used a systematic review following PRISMA guidelines. Articles sourced from EBSCOhost, Google Scholar, and Taylor and Francis. After reading the abstracts and conducting further searches, the authors identified 6 articles for systematic review. Researchers found that the barcode link-based module had a positive impact on learning. Most of the research articles were found in national journals, and most of the research was conducted on the islands of Java and Sulawesi. However, further analysis shows the need for growth in theoretical frameworks, development in other fields, and the availability of learning materials for research into learning media development, such as in chemistry education.